1995
DOI: 10.1136/adc.72.1.33
|View full text |Cite
|
Sign up to set email alerts
|

DNA testing for fragile X syndrome in schools for learning difficulties.

Abstract: (Arch Dis Child 1995; 72: 33-37)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 21 publications
3
17
0
Order By: Relevance
“…The confidence limits, available for only four of these studies, vary widely, with a lower boundary of 1 in 1,333 40 to an upper boundary of 1 in 8,922. 41 Three studies summarized in Table 1 did not report point estimates: two 42,43 provided a range and one 44 provided a lower boundary, all of which fall within the point estimates and confidence intervals reported in the other studies ( Table 1).…”
Section: Full Mutation and Males: Caucasian Populations Of Northern Ementioning
confidence: 51%
See 1 more Smart Citation
“…The confidence limits, available for only four of these studies, vary widely, with a lower boundary of 1 in 1,333 40 to an upper boundary of 1 in 8,922. 41 Three studies summarized in Table 1 did not report point estimates: two 42,43 provided a range and one 44 provided a lower boundary, all of which fall within the point estimates and confidence intervals reported in the other studies ( Table 1).…”
Section: Full Mutation and Males: Caucasian Populations Of Northern Ementioning
confidence: 51%
“…Millan et al 43 also acknowledged that persons with mild MR might have been missed, so the range could be as high as 1/5,000 -1/6,800. h Slaney et al 44 only provided a lower boundary, not a point estimate.…”
Section: Disease(s)mentioning
confidence: 99%
“…A class III prospective study of 103 males with moderate to severe learning difficulties yielded a 3.9% incidence among males for the FMR1 mutation using molecular techniques. 55 Pooled data (see table 2, bottom) from seven studies involving 785 females with varying degrees of mental retardation found an incidence of the fragile X mutation of 2.5%. [48][49][50][51][52][53][54] In a more recent study of 2,757 individuals with mental retardation, 2.6% had fragile X mutations and one-third of these individuals were female.…”
mentioning
confidence: 99%
“…It helps identifying carriers of the disease and offers a possibility of its prevention, and regarding the child with the fragile X syndrome it provides an opportunity for a better understanding and proper treatment of these individuals. Moreover, genotype/phenotype studies in fragile X individuals contributed to the evaluation of the high risk phenotype for more selective fragile X detection that would increase the proportion of positive cases and would therefore contribute to cost-effectiveness of such screening [6, 20, 25, 29]. …”
Section: Discussionmentioning
confidence: 99%
“…Fragile X screening programmes have been extensively used to estimate the prevalence of the fragile X syndrome and to identify unrecognised cases [4, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24]. Moreover, genotype/phenotype correlations in fragile X individuals contributed to the evaluation of the high risk phenotype for a more selective fragile X detection [6, 19, 25].…”
Section: Introductionmentioning
confidence: 99%